Reducing time to angiography and hospital stay for patients with high-risk non-ST-elevation acute coronary syndrome: retrospective analysis of a paramedic-activated direct access pathway. Issue 6 (20th June 2016) - Koganti, S; Patel, N; Seraphim, A; Kotecha, T; Whitbread, M; Rakhit, R D
Abstract : Objective: To assess whether a novel 'direct access pathway' (DAP) for the management of high-risk non-ST-elevation acute coronary syndromes (NSTEACS) is safe, results in 'shorter time to intervention and shorter admission times'. This pathway was developed locally to enable London Ambulance Service to rapidly transfer suspected high-risk NSTEACS from the community to our regional heart attack centre for consideration of early angiography. Methods: This is a retrospective case–control analysis of 289 patients comparing patients with high-risk NSTEACS admitted via DAP with age-matched controls from the standard pan-London high-risk ACS pathway (PLP) and the conventional pathway (CP). The primary end point of the study was time from admission to coronary angiography/intervention. Secondary end point was total length of hospital stay. Results: Over a period of 43 months, 101 patients were admitted by DAP, 109 matched patients by PLP and 79 matched patients through CP. Median times from admission to coronary angiography for DAP, PLP and CP were 2.8 (1.5–9), 16.6 (6–50) and 60 (33–116) hours, respectively (p<0.001). Median length of hospital stay for DAP and PLP was similar at 3.0 (2.0–5.0) days in comparison to 5 (3–7) days for CP (p<0.001). Conclusions: DAP resulted in a significant reduction in time to angiography for patients with high-risk NSTEACS when compared to existing pathways.